Construction and Validation of an Aptitude Test for Pre-service Teachers on Inclusive Education - Mistry, H.S. (INDIAN EDUCATIONAL REVIEW, 2020)
This paper describes the development and validation of a measure of pre-service teachers’ teaching aptitude towards inclusive education of students with disabilities. Five factors, namely— knowledge about inclusive education, perceived ability to identify disabilities, attitude towards teaching children with disabilities, perceived ability to adapt inclusive teaching methods and skills to manage the inclusive classroom were tested. Fifty items were constructed under the listed five factors and the test was implemented on 552 pre-service teachers of Gujarat state. The test was found to be a reliable and valid tool for measuring pre-service teachers’ teaching aptitude towards inclusive education.